2021
DOI: 10.1021/acscatal.1c02076
|View full text |Cite
|
Sign up to set email alerts
|

Toward Reproducible Enzyme Modeling with Isothermal Titration Calorimetry

Abstract: To apply enzymes in technical processes, a detailed understanding of the molecular mechanisms is required. Kinetic and thermodynamic parameters of enzyme catalysis are crucial to plan, model, and implement biocatalytic processes more efficiently. While the kinetic parameters, K m and k cat , are often accessible by optical methods, the determination of thermodynamic parameters requires more sophisticated methods. Isothermal titration calorimetry (ITC) allows the label-free and highly sensitive analysis of kine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Since all aspects lead to a lack of experimental reproducibility, insufficient standardization and inconsistencies in data management are particularly troubling and hamper further development of the field [4d,5,28] . To improve reproducibility and credibility of experimental studies, various efforts to implement guidelines, such as the National Research Data Infrastructure Consortium (NFDI, https://nfdi.de), [29] are recently being applied in biocatalysis research [30] …”
Section: Advances and Challenges In The Analysis Of Dna‐based Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all aspects lead to a lack of experimental reproducibility, insufficient standardization and inconsistencies in data management are particularly troubling and hamper further development of the field [4d,5,28] . To improve reproducibility and credibility of experimental studies, various efforts to implement guidelines, such as the National Research Data Infrastructure Consortium (NFDI, https://nfdi.de), [29] are recently being applied in biocatalysis research [30] …”
Section: Advances and Challenges In The Analysis Of Dna‐based Cascadesmentioning
confidence: 99%
“…[4d,5,28] To improve reproducibility and credibility of experimental studies, various efforts to implement guidelines, such as the National Research Data Infrastructure Consortium (NFDI, https://nfdi.de), [29] are recently being applied in biocatalysis research. [30]…”
Section: Advances and Challenges In The Analysis Of Dna-based Cascadesmentioning
confidence: 99%
“…The wide field involving ITC to study protein-protein or protein-ligand (metal ion, inhibitor, cofactor) interactions, thermodynamics of membrane proteins, as well as the study of protein stability are excluded from this review, but excellent reviews can be found elsewhere (Freire et al, 1990;Jelesarov and Bosshard, 1999;Ward and Holdgate, 2001;Holdgate, 2001;O'Brien and Haq, 2004;Grossoehme et al, 2010;Draczkowski, et al, 2014;Rajarathnam and Rösgen, 2014;Quinn, et al, 2016). A number of (tutorial) reviews on the study of enzyme kinetics using ITC are already available (Todd and Gomez, 2001;O'Brien and Haq, 2004;Bianconi, 2007;Demarse et al, 2013;Quinn and Hansen, 2019;Wang, et al, 2020;Ott, et al, 2021). The focus of this minireview is to cover developments in enzyme calorimetry that are relevant for the biocatalysis field.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an induced fit mechanism has been proposed for Gre2p, which leads to a conformational change of the active site upon NADPH binding. 17 This process could be decelerated by immobilizing Gre2p on DON. Additionally, the high negative charge density on DON as well as tight packing on beads could lead to a changed local environment and thus result in unfavorable interactions between Gre2p and DON.…”
mentioning
confidence: 99%